Hubungan Filsafat Pendidikan dan Kebudayaan - Muhamad Rizki Sahriya Ramadan; Salsha Tria Maharani; Fatihatul Muflihah; Dina Indriana; Wahyu Hidayat (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This article discusses the concept of educational philosophy, explains the relationship between philosophy and educational theory, as well as the relationship between philosophy, education and culture. Educational philosophy is seen as a structured thinking process that uses philosophy as a guide in organizing, aligning, and integrating steps in education. The article also details definitions from several experts, such as Al-Syaibany, John Dewey, and Imam Barnadib, who describe educational philosophy as a philosophical analysis of education. In relation to educational theory, the article explains that educational philosophy conveys its philosophical principles to educational theory, often facing challenges that require contributions from educational philosophy. In addition, the article outlines the relationship between philosophy and culture, where culture is considered as a manifestation of human nature, and philosophy as a systematic and universal method of thinking that includes every soul. Finally, the article presents a view on the relationship between education and culture, describing education as a philosophical activity that aims to explain, harmonize, assess and change the educational process by considering cultural issues. Education is considered to have a dual responsibility, namely developing individual potential and preserving cultural values, which are sustainable and provide mutual support.